Oral manifestations of sexually transmitted diseases identified in three stomatology services in South America - Carmona-Lorduy, Martha; Porto-Puerta, Ivan; Lanfranchi, Hector; Medina-Carmona, Wanda; Werner, Laura; Maturana, Stella (Universidad y Salud, 2018)
Introduction: Sexually transmitted diseases are defined as a group of infections caused by various agents which are acquired during sexual intercourse. They also tend to generate manifestations in the mouth. Objective: To determine the typical lesions in oral cavity of sexually transmitted diseases. Materials and methods: A descriptive transversal study was conducted with 37 patients who attended the stomatology services of the University of Buenos Aires, University of Cartagena and the Aleman Hospital in Buenos Aires during 2015 and 2016. A complete clinical history was carried out with Venereal Disease Research Laboratory (VDRL) and Fluorescent Treponemal Antibody Absortion (FTA-ABS) tests in patients with presumption of syphilis. In addition, histopathological analysis and Polymerase Chain Reaction (PCR) was made in patients with presumption of Human papillomavirus (HPV). Results: The average age of the patients was 38, where male sex predominated. 54.1% were diagnosed with syphilis and the most found lesion in them was the papule. The remaining 45.9% were diagnosed with HPV, the predominant lesion in them was a wart. Conclusions: The dentist should contribute to the early detection of sexually transmitted diseases by identifying manifestations of these in the mouth in order to prevent their evolution and prevent their transmission.